FACTORS INFLUENCING THE INTENTION TO ACCEPT E-GOVERNMENT IN MALAYSIA: A STRUCTURAL EQUATION MODELLING APPROACH - ADEGBITE TAIWO, AYANKUNLE (2012)
Despite huge financial and structural investment on eGovernment strategies, application development and provision of online public services to citizens, Malaysia still encounter daunting challenges in relation to the acceptance and use of the eGovernment services by its citizens. In addition, empirical studies on the acceptance of eGovernment have been given little attention. The objective of the present research is to examine citizens' intention towards the acceptance of eGovernment by investigating the interaction between WebTrust, Technology perception (UTAUTPerformance Expectancy, Effort Expectancy, Social Influence, and Facilitating Conditions), Internet anxiety, Risk taken, Attitude towards Internet and Behavioural Intention in predicting the acceptance of eGovernment in Malaysia.